Artificial Intelligence in Surgical Decision-Making: A Comprehensive Review of Applications Across the Preoperative, Intraoperative, and Postoperative Continuum - Dr. N. Junior Sundresh MS, FRCS, FACS, Dr. Jayaraman MS, Dr. Shukla Bikku, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Artificial intelligence (AI) and machine learning (ML) are increasingly embedded across the surgical care pathway, moving beyond early risk-scoring tools toward real-time intraoperative guidance, automated complication prediction, and clinical decision support for multidisciplinary oncologic planning. Whether this expanding footprint translates into genuinely improved surgical decision-making-as opposed to impressive but clinically unvalidated model performance-remains an open and actively debated question.